KOORDINASI PEMERINTAHAN DALAM MENUNJANG KEWENANGAN OTONOMI DESA - Listiana Padagi E.42008023 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This study is intended to produce a recommendation how to realize an effective coordination withinthe Village Government in particular coordination between the village government and the BPD in thevillage of Stone Tumbles Sharply Titi Ketapang District. The title of this thesis based on the issues raisedin the village of Batu Sharp that the conflict between the village and the BPD, discrepancies anddiscrepancies of opinion in the process of drafting regulations to determining APBDes and village.This study used a qualitative research model by using the theory of coordination "Tripathi andReddy", explained that there are four important factors to achieve an effective coordination. The fourfactors are: communication, leadership, continuity and formulation of authority and responsibility, if thefour factors can be realized with better then expected result that an effective coordination can be realized.The research location in the village of Batu Sharp. The subjects were the village government and itsDevices and Chairman and members of the BPD.The conclusion of this research is the lack of coordination between the village and the BPD in thetasks and functions together to lead to conflict between the two sides. For that recommendation as well asthe solutions given to achieve an effective coordination and harmonious relationships are 4 factors of"Tripathi and Reddy" intensify the communication, the role of leadership, continuity and provide anexplanation of the importance of understanding the duty and function of each.Keywords : coordination and authority of village autonomy